2016
DOI: 10.1002/2016gb005421
|View full text |Cite
|
Sign up to set email alerts
|

The anthropogenic perturbation of the marine nitrogen cycle by atmospheric deposition: Nitrogen cycle feedbacks and the 15N Haber‐Bosch effect

Abstract: Over the last 100 years, anthropogenic emissions have led to a strong increase of atmospheric nitrogen deposition over the ocean, yet the resulting impacts and feedbacks are neither well understood nor quantified. To this end, we run a suite of simulations with the ocean component of the Community Earth System Model v1.2 forced with five scenarios of nitrogen deposition over the period from 1850 through 2100, while keeping all other forcings unchanged. Even though global oceanic net primary production increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 95 publications
(161 reference statements)
9
92
2
Order By: Relevance
“…The effects of atmospheric deposition have been evaluated previously using global ocean biogeochemical models [ Krishnamurthy et al ., , , ; Suntharalingam et al ., ; Yang and Gruber , ] or based on various scaling procedures by Duce et al . [].…”
Section: Impacts Of Atmospheric Deposition On Water Column Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of atmospheric deposition have been evaluated previously using global ocean biogeochemical models [ Krishnamurthy et al ., , , ; Suntharalingam et al ., ; Yang and Gruber , ] or based on various scaling procedures by Duce et al . [].…”
Section: Impacts Of Atmospheric Deposition On Water Column Productivitymentioning
confidence: 99%
“…[], Suntharalingam et al . [], Yang and Gruber [], and Krishnamurthy et al . [] have recently provided estimates of atmospheric inputs of fixed nitrogen to the world oceans and the impact of this deposition on ocean biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The function has been coupled to Earth System Models to predict benthic denitrification in the modern ocean (e.g., Somes et al, 2013;Yang and Gruber, 2016). The function is also dynamic in the sense that N loss responds instantaneously to changes in the boundary conditions, but does not consider the storage of solutes and particulates in sediments.…”
Section: Benthic-pelagic Coupling and N Loss On The Marginmentioning
confidence: 99%
“…Indirect alterations include activities that increase the atmospheric concentration of greenhouse gases, leading to ocean warming, acidification and deoxygenation (Hutchins and Fu, 2017). The scale and impact of such anthropogenic perturbation of the marine N cycle remain highly uncertain (Gruber, 2016;Hutchins and Fu, 2017). 25 Estimated anthropogenic release of N into the global environment (~160 Tg N yr -1 ) is now of similar magnitude to all natural global ocean N 2 fixation (~140 Tg N yr -1 ), and may increase along with growing global population (Eugster and Gruber, 2012;Gruber and Galloway, 2008).…”
Section: Effects Of Anthropogenic Activity On the Marine Nitrogen Cycmentioning
confidence: 99%
“…Modeling studies have shown that the predicted anthropogenic increase in atmospheric N deposition could initiate a series of strong negative feedback in the marine N cycle. There could be a pronounced decrease in global ocean N 2 fixation and an increase in denitrification, which would compensate for much of the enhanced N input 30 and limit the impact of atmospheric N deposition on marine productivity (Somes et al, 2016;Yang and Gruber, 2016 Ocean warming enhances water stratification and decreases oxygen solubility, causing a major loss of O 2 from the future ocean (Dybas, 2005). Worldwide expansion of dead zones and OMZs will have large impacts on microbially mediated N processes in marine ecosystems.…”
Section: Effects Of Anthropogenic Activity On the Marine Nitrogen Cycmentioning
confidence: 99%